Research on the path of practical cooperation between China and European Union countries under the environment of carbon neutrality and peak carbon dioxide emissions - Cai, Wangang (Frontiers in Ecology and Evolution, 2023)
.Globalization is increasing daily with the development of the world economy and society. International conflicts, cooperation, and interdependence in international environmental relations have become increasingly prominent, laying a theoretical and practical basis for international environmental cooperation. The environmental protection industries of China and the EU (European Union) are facing great development opportunities. Many EU member states have their advantages in developing the environmental protection industry, which facilitates all-around cooperation in the environmental protection industry with my country. Based on the target policy background of PCDE (peak carbon dioxide emissions) and CN (carbon neutrality) and domestic and foreign research, this paper proposes a study on the practical cooperation path between China and EU countries. Based on international input-output data, an economic output CDE (carbon dioxide emission) matrix is constructed to characterize the economic and CDE correlation between countries, thus forming an international CDE network. The analysis shows that the contribution rate of energy structure effect and energy intensity fluctuates slowly, showing a positive and negative alternation; Our government should adopt an active energy optimization policy, speed up the formulation of macro policies such as carbon tax on energy-consuming industries, continuously optimize the energy structure and reduce the CDE intensity. By 2023, China's unit GDP will remain the same by 40%-50% compared with 2022.